Implementation of Standard Operating Procedures and Circular Economy as an Integrated Waste Management Strategy - Wulandari, Cahyo; Kamalia, Isna; Alifiany, Andini Cahya; Widodo, Meidita Farah (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Waste management in coastal areas remains a crucial issue that significantly affects environmental quality and public health if not addressed in an integrated manner. Dukuh Tambak Gojoyo in Wedung Village is one of the areas with high household waste production. However, waste management is not yet optimal, especially in terms of facilities, infrastructure, and institutions. This situation directly contributes to the accumulation of waste in the environment, increased potential for pollution, and weakened public awareness due to the absence of a clear, targeted, and accessible management system. This community service program aimed to improve awareness, skills, and participation of local residents in waste management through technical, participatory, and innovative approaches. The methods employed included field surveys, interviews, focus group discussions, socialization, and practical waste management activities. The program achieved several key outcomes: (1) the formulation of a standard operating procedure for waste management as a technical guideline for the community; (2) mapping of waste generation points to identify priority areas for waste bin placement (15 waste generation points were identified); (3) provision of inorganic waste bins at identified waste generation points, totaling 5 units of waste bins; and (4) the application of a circular economy concept through the utilization of organic waste into local microorganisms and compost, accompanied by an increase in pretest scores from 5,1 to posttest score of 10, indicating a significant improvement in participant’s understanding of the circular economy concept. The economic estimation shows that MOL production provides potential profit of IDR 6.000.000, while compost production yields an estimated selling value of IDR 35.000 per package. Overall, the implemented program demonstrates the potential of community-based waste management, supported by adequate facilities, infrastructure, and circular economy practices, as an effective strategy to reduce waste generation, strengthen environmental awareness, and create cleaner, healthier, and more sustainable residential environments